Designing an Interactive Video Based Learning Tool Using Minecraft to Enhance Arabic Reading Skills in Modern Islamic Boarding School - Moh. Ilham Fahreza; Alif Cahya Setiyadi; Tiara Eki Wahyu Rinawati (Universitas Islam Negeri Palangka Raya Raya, 2026)
Arabic language instruction has long been a priority at Islamic Modern Boarding School Darussalam Gontor For Girls Campus 3. Among the core subjects is Muthola’ah, which emphasizes reading comprehension of Arabic texts, especially for firstyear intensive students with three sessions per week. However, observations indicate a lack of student engagement and motivation, partly due to the absence of interactive learning media. To address this, the present study aims to develop a video based instructional medium utilizing Minecraft to enhance students Arabic reading proficiency. This research employs the Research and Development (R&D) method following the ADDIE model, involving needs analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, tests, questionnaires, and documentation, with a quantitative analysis conducted using paired sample t tests. Findings demonstrate that the Minecraft based video significantly improves students reading skills, as evidenced by a notable increase in posttest scores. Furthermore, students responded positively to the media, highlighting its engaging nature and its capacity to make Arabic texts more accessible. The study contributes to the field of Arabic language education by integrating gamification elements into language instruction, offering a practical and innovative approach for enhancing reading comprehension in Islamic boarding school settings.